The Ruin of Ruins: Preservation and the Loss of Value - Raymond Streeter (Oz, 1985)
On April 4, 1979, concerned students and faculty gathered in front of Nichols Gymnasium to protest the imminent destruction of its remains. The structure stood in a ruinous state since its immolation ten years earlier…